Social rights in Colombia and the principle of financial sustainability - Lopez Daza, German (DIXI, 2013)
The main characteristic that differentiates social or second-generation rights is that they force the state to provide services like health, education, housing, or social security. As a historical category among fundamental rights, these rights have had an important constitutional development in many legal systems, including the Colombian system. The problem of justice concerning these rights has led the Colombian government to enact a constitutional reform that established the principle of financial sustainability, whose originality has led to many questions on its applicability and constitutionality.
Keywords: Judiciary activism; economic; , social and cultural rights; social rights judicialization; budgetary sustainability